Head Injury Prevalence in a Population of Injured Patients Seeking Care in Ghana, West Africa - Baiden, Frank; Anto-Ocrah, Martina; Adjei, George; Gyaase, Stephaney; Abebrese, Jacob; Punguyire, Damien; Owusu-Agyei, Seth; Moresky, Rachel T. (Frontiers in Neurology, 2022)
Background/Significance: Much of the literature on head injury (HI) prevalence comes from high-income countries (HICs), despite the disproportionate burden of injuries in low to middle-income countries (LMICs). This study evaluated the HI prevalence in the Kintampo Injury Registry, a collaborative effort between Kintampo Health Research Centre (KHRC) in Ghana and the sidHARTe Program at Columbia University Mailman School of Public Health. In our first aim, we characterize the HI prevalence in the registry. In aim 2, we examine if there are any sex (male/female) differences in head injury outcomes in these populations for points of potential intervention. Methods Secondary analysis of data from the Kintampo Injury Registry which had 7,148 registered patients collected during January 2013 to January 2015. The definition of a case was adopted to ensure consistency with the International Statistical Classification of Diseases and Related Health Problems, revision 10 (ICD-10). A 3-page questionnaire was used to collect data from injured patients to include in the registry. The questions were designed to be consistent with the World Health Organization (WHO) guidelines on injury surveillance and were adapted from the questionnaire used in a pilot, multi-country injury study undertaken in other parts of Africa. The questionnaire collected information on the anatomic site of injury (e.g., head), mechanism of injury (e.g., road traffic injuries, interpersonal injuries (including domestic violence), falls, drowning, etc.), severity and circumstances of the injury, as well as precipitating factors, such as alcohol and drug use. The questionnaire consisted mainly of close-ended questions and was designed for efficient data entry. For the secondary data analyses for this manuscript, we only included those with “1st visit following injury” and excluded all transfers and follow-up visits (n = 834). We then dichotomized the remaining 6,314 patients to head injured and non-head injured patients based on responses to the variable “Nature of injury =Head Injury”. We used chi-square and Fisher's exact tests with p < 0.05 as cut-off for statistical significance. Logistic regression estimates were used for effect estimates. Results Of the 6,314 patients, there were 208 (3.3%) head-injured patients and 6,106 (96.7%) patients without head injury. Head-injured patients tended to be older (Mean age: 28.9 +/-13.7; vs. 26.1 +/- 15.8; p = 0.004). Seven in 10 head injured patients sustained their injuries via transport/road traffic accidents, and head-injured patients had 13 times the odds of mortality compared with those without head injuries (OR: 13.3; 95% CI: 8.05, 22.0; p < 0.0001) even though over half of them had mild or moderate injury severity scores (p < 0.001). Evaluation of sex differences amongst the head-injured showed that in age-adjusted logistic regression models, males had 1.4 times greater odds of being head injured (OR: 1.4; 95% CI: 1.04, 2.00; p = 0.03) and over twice the risk of mortality (OR: 2.7; 95% CI: 0.74, 10.00; p = 0.13) compared to females. Conclusion In these analyses, HI was associated with a higher risk of mortality, particularly amongst injured males; most of whom were injured in transport/road-traffic-related accidents. This study provides an impetus for shaping policy around head injury prevention in LMICs like Ghana.